Intergroup Conflict Management Strategies From a Nobel Peace Laureate: The Case of José Ramos-Horta. Issue 6 (1st November 2016) - Filho, Edson; Rettig, Jean
ABSTRACT: We report on the case of Dr. José Ramos-Horta (JRH), a 1996 Nobel Peace Laureate, former President of East Timor, and current envoy of the United Nations to Guinea-Bissau. JRH agreed to an interview detailing the peace-building strategies he has used to manage conflicts. The transcript of his Nobel Laureate acceptance speech was also analyzed to strengthen the overall narrative. Our qualitative analysis revealed two higher order themes: psycho-social skills and social networking. Specifically, JRH uses active listening, mindful breaks, and awareness of media trends to create personal and strategic networking contacts, which are critical elements in managing conflict.